Effects of animated pedagogical agent-guided loving-kindness meditation on flight attendants’ spirituality, mindfulness, subjective wellbeing, and social presence - Liu, Chao; Chen, Hao; Zhou, Fang; Chiang, Chao-Hung; Chen, Yi-Lang; Wu, Kan; Huang, Ding-Hau; Liu, Chia-Yih; Chiou, Wen-Ko (Frontiers in Psychology, 2022)
Loving-kindness meditation (LKM) was first practiced by Buddhists and then developed by clinical psychologist. Previous studies on LKM have mainly focused on the impact of real person-guided meditation on depression, anxiety, and other negative psychology. During the COVID-19 pandemic, this study explored the effect and mechanism of media-guided LKM on the improvement of social presence, mindfulness, spirituality, and subjective wellbeing (SWB). From the viewpoint of positive psychology, this study compared the different media effects of animated pedagogical agent (APA)-guided LKM and audio-guided LKM. A total of 82 flight attendants were recruited from airlines; then, they were randomly assigned to two groups: APA group (41 participants) and audio group (41 participants), which both underwent an 8-week LKM training intervention. The aforementioned four main variables were measured pre and post the meditation experiment. The results indicated that both APA-guided meditation and audio-guided meditation significantly improved subjects’ spirituality and SWB. Compared with audio-guided meditation, APA-guided meditation significantly improved the subjects’ spirituality, SWB, and social presence. Audio-guided meditation has no significant effect on social presence. This study highlights APA-guided meditation has a positive effect on spirituality, SWB, and social presence, which may provide individuals with a simple and easy method to improve their mental health.